Optimalisasi Penggunaan Conveyor Belt Dalam Menunjang Pelayanan Di Bandar Udara Internasional Syamsudin Noor Banjarmasin - Ahmad Riyanda Faisol Ibad; Djoko Widagdo (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study examines the optimization of conveyor belt usage in supporting passenger services at Syamsudin Noor International Airport, Banjarmasin. Conveyor belt is one of the important facilities in handling luggage that has a crucial role in accelerating the process of handling goods and reducing passenger waiting time. The less than optimal use of conveyor belts at Syamsudin Noor International Airport causes less than optimal passenger service, especially causing a buildup of passengers in the arrival terminal area. Therefore, the author conducted this research with the aim of finding out the causes of non-optimal use of conveyor belts at Syamsudin Noor Airport and the solutions that must be implemented to overcome them.This research was conducted from January 31 to February 10 2024 at Syamsudin Noor International Airport, Banjarmasin. This research uses qualitative research methods in the form of primary and secondary data. Primary data in this research was obtained from interviews conducted with 1 technical officer and 2 Terminal Service Officers. Meanwhile, secondary data in this research was obtained from literature reviews and journals related to this research. Qualitative data analysis techniques used include Data Reduction, Triangulation, and Drawing Conclusions. The research results show that optimizing and increasing conveyor belt capacity as well as implementing automatic monitoring and maintenance technology can reduce the risk of operational disruption and increase passenger satisfaction. This research also identifies solutions for terminal service area officers and mechanics to improve conveyor belt conditions that are not optimal, where the solutions suggested by the author include replacing rollers and pulleys, cleaning and lubricating components, and applying strengthening techniques.